1998
DOI: 10.1046/j.1365-2362.1998.00342.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of air pollutants on the pulmonary surfactant system

Abstract: Air pollutants have been recognized to influence the structure and function of the surfactant system. Agents that have received the most attention include ozone, nitrogen dioxide, hyperoxia, diesel exhaust, tobacco smoke, silica and fibrous materials such as asbestos. The deleterious effects of air pollutants on the surfactant system depend on the size of the agent, on its solubility in aqueous solutions and chemical reactivity and on its concentration and the duration of exposure. Hereby the following general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 147 publications
(187 reference statements)
1
32
0
1
Order By: Relevance
“…Early studies in animal models indicated a general increase in surfactant volume, but not composition in response to silica [12,13], which according to Muller et al, is unique to silica inhalation compared to tobacco smoke and diesel particles [14]. One study found 3-7 fold increases in PL and SP, respectively, occurring in a rat model with acid-washed silica, but not with unwashed silica [15].…”
Section: Effect Of Silica Exposure On Lung Surfactantmentioning
confidence: 99%
“…Early studies in animal models indicated a general increase in surfactant volume, but not composition in response to silica [12,13], which according to Muller et al, is unique to silica inhalation compared to tobacco smoke and diesel particles [14]. One study found 3-7 fold increases in PL and SP, respectively, occurring in a rat model with acid-washed silica, but not with unwashed silica [15].…”
Section: Effect Of Silica Exposure On Lung Surfactantmentioning
confidence: 99%
“…It is possible that the increased sensitivity to infection that some individuals exhibit after ozone exposure, as assessed by higher risk of common infections in areas with highly polluted air (42), may reflect the involvement of intrinsic or genetic factors and/or the functional impairment of oxidant-exposed SP-A. Different individuals may possess different combinations of SP-A variants and proportions of SP-A1 and SP-A2 content (52).…”
mentioning
confidence: 99%
“…Air pollutants have also been recognized to influence the structure and function of the lung surfactant system (6,7). Oxidative inactivation of surfactant by cellular reactive oxygen species (ROS), leading to surfactant lipid peroxidation, protein carbonylation, and functional impairment of surfactant protein A, are thought to be possible mechanisms underlying air pollutantinduced surfactant damage (7)(8)(9)(10)(11). Oxidative damage to lung epithelial cells is a component of acute lung injury and associated respiratory failure (12).…”
mentioning
confidence: 99%